The Role of the National Narcotics Agency in Preventing Narcotics Distribution in North Labuhanbatu Regency (A Research Study in North Labuhanbatu Regency) - Roni Septian Butar-Butar; Harun H; Hasan Basri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The expanding circulation of narcotics in North Labuhanbatu Regency, reaching rural areas and involving various age groups, reflects alarming social conditions and weak state oversight, contradicting the state’s duty to protect the public under Law No. 35 of 2009 on Narcotics. This study aims to analyze the role of the North Labuhanbatu Regency National Narcotics Agency (BNNK) in preventing narcotics distribution and to identify the obstacles faced in its implementation. Using an empirical juridical method through literature review and field interviews, the study finds that widespread narcotics circulation is driven by easy access through organized networks, weak supervision in remote areas, limited public education, and challenging geographic conditions, all contributing to rising crime rates and social deterioration. The novelty of this research lies in emphasizing the need for comprehensive interventions that position BNNK not only as an enforcement body but also as a community-centered prevention coordinator. The study concludes that although BNNK has conducted outreach, rehabilitation, and enforcement operations, effectiveness remains hindered by limited human resources, budget constraints, insufficient facilities, and low community participation. It is recommended to strengthen institutional capacity, improve cross-sector collaboration, and encourage sustained community involvement to build resilience against narcotics circulation.